2016
DOI: 10.3399/bjgp16x685633
|View full text |Cite
|
Sign up to set email alerts
|

Patients with cancer and change of general practice: a Danish population-based cohort study

Abstract: BackgroundGeneral practice plays an important role in the cancer care pathway. Patient dissatisfaction with the diagnostic process may be expressed by changing to another general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…A study has shown that patients with cancers that are “hard‐to‐detect” more frequently changed GP around the time of diagnosis compared to other cancer patients (Grooss, Hjertholm, Carlsen, & Vedsted, ). This may indicate dissatisfaction with timeliness and the diagnostic pathways, which is supported by the results of this survey.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that patients with cancers that are “hard‐to‐detect” more frequently changed GP around the time of diagnosis compared to other cancer patients (Grooss, Hjertholm, Carlsen, & Vedsted, ). This may indicate dissatisfaction with timeliness and the diagnostic pathways, which is supported by the results of this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Although dissatisfaction with the diagnostic pathway of PD appears to be playing a limited role in quantitative terms, dissatisfaction with the initial diagnostic process can have an impact on long-term care, stressing the importance of paying attention to it: cognitions formed at an early stage tend to determine care experiences during the further treatment episode [ 2 , 5 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to assess the relation between dissatisfaction with the diagnostic pathway and a selection of factors. These factors were selected based on literature [ 5 , 18 ], the results of the preceding qualitative analysis [ 16 ] and expert opinion. The χ 2 test was used to assess the relation between dissatisfaction and the demographic variables sex and level of education, the latter divided into low (primary school/vocational education), medium (secondary school) and high (higher professional education/university).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008), ASCO-ESMO (2006), ACoSCo (2016), Edwards (2016), National Quality Forum (NQF) (2009), Grunfeld et al (2008), Jensen, Torring et al (2014), Jensen et al (2016), Levit et al (2013), Parker et al (2007), Raval et al (2010), Vargas, Ryan, Jackson, Rodriguez, and Freeman al. (2008), Almeida et al (2013), Arrighi et al (2015), ASCO (2006), Barocas and Penson (2010), Burmeister et al (2016), ACoSCo (2016), Earle (2007), Feld and Feld (2010), Forum (2009), Grunfeld et al (2008), Holland and Weiss (2008), Holland, Watson, and Dunn (2011), Langer and Stern (2007), Lebeau et al (2011), Levit et al (2013), Manchon-Walsh et al (2011), Mano et al (2008), Mathis and Cima (2014), Meert and Sculier (2008), Numico et al (2014), Ost, Niu, Elting, Buchholz, and Giordano (2014), Pagano et al (2010), Raval et al (2010), Rizzo et al (2011), Saini et al (2016), Samson, Porter, Hurley, Adams, and Eberth (2016), Schrader et al (2010), Spencer et al (2008), Stordeur et al (2015), Taflampas et al (2008), van de Velde et al (2013), Wang et al ), AielloBowles et al (2008),Anderson (2016),Arrighi et al (2015),ASCO (2006),Burmeister et al (2016),Earle (2007),Grooss, Hjertholm, Carlsen, and Vedsted (2016),Grunfeld et al (2008),Holland and Weiss (2008),Lamb, Brown, et al (2011), Lamb, Sevdalis, Mostafid, Vincent, and Green (2011), Lamb, Sevdalis, Vincent, and Green (2012,Lebeau et al (2011),Levit et al (2013),Nazareth et al (2008), NQF (2009),Riquet et al (2013),Rizzo et al (2011), Stordeur et al (2015,Tremblay et al (2011), Vargas et al (2008,Wang et al (2012)…”
mentioning
confidence: 99%